Development of Arabic Conversation Material Based on Communicative-Interactive Approach/ Pengembangan Materi Percakapan Bahasa Arab Berbasis Pendekatan Komunikatif-Interaktif Bagi Mahasiswa - Hamid, M. Abdul; Fatimah, Siti (Ijaz Arabi Journal of Arabic Learning, 2020)
This research and development aimed at producing an Arabic conversation textbook for students at Arabic Intensive Program (PKPBA) UIN Malang to help their learning process becomes more accessible and funnier based on the communicative-interactive approach and reveals its viability. The method of this research was research and development (RD), which was proposed by Dick and Carey. The design of the product trial went through the expert validation, linguist and instructional design expert. The data were analyzed as quantitative and qualitatively. The results of this research indicated that the Arabic conversation textbook for PKPBA students has been developed in accordance with procedures and the themes determination were based on the need analysis so that it becomes a real and meaningful theme for student's life and activities, including: introduction, conversation around campus (faculty, study program, administration, classroom, library, sport center, canteen, parking lot, mosque, dormitory/ma'had), shopping activity, being in the hospital, and tourism place. The trial results of the material components of the conversation showed that: the content experts rated the product development as very good and feasible, while the instructional design experts assessed that most parts of the teaching material are very reasonable. Also, individual trial subjects considered that most components of the learning material are excellent. The Arabic lecturers discussed most of the textbook components are very feasible, and the issues of field trials also rated them very well.